2019
DOI: 10.3390/molecules24234397
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Dopamine) Coating on 3D-Printed Poly-Lactic-Co-Glycolic Acid/β-Tricalcium Phosphate Scaffolds for Bone Tissue Engineering

Abstract: Bone defects caused by osteoporosis, bone malignant tumors, and trauma are very common, but there are many limiting factors in the clinical treatment of them. Bone tissue engineering is the most promising treatment and is considered to be the main strategy for bone defect repair. We prepared polydopamine-coated poly-(lactic-co-glycolic acid)/β-tricalcium phosphate composite scaffolds via 3D printing, and a series of characterization and biocompatibility tests were carried out. The results show that the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 39 publications
2
57
0
Order By: Relevance
“…The scaffold should constitute a template which promotes extracellular matrix formation and a place for osteoblasts to adhere and proliferate. Such biomaterials can have a form of nanofibers, hydrogels, metal alloys, β-TCP, HA powders, and granules or bioactive glasses [10,11]. Among them, the most promising ones are nanofibrous scaffolds, which can be prepared through electrospinning of the polymer solution since they biomimic natural ECM architecture [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scaffold should constitute a template which promotes extracellular matrix formation and a place for osteoblasts to adhere and proliferate. Such biomaterials can have a form of nanofibers, hydrogels, metal alloys, β-TCP, HA powders, and granules or bioactive glasses [10,11]. Among them, the most promising ones are nanofibrous scaffolds, which can be prepared through electrospinning of the polymer solution since they biomimic natural ECM architecture [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning enables preparation of micro-and nanofibers, using both raw polymers solution as well as composites and nanocomposites [19]. To enhance NFs properties, ready products may undergo postprocessing functionalization by various substances, such as hydroxyapatite, β-TCP, metal, or metal oxide nanoparticles [5,9,10,[25][26][27]. Such an approach enables preparation of bone-tissue scaffolds with tunable properties, including programmed biodegradability rate, enhanced mechanical durability, crystallinity, antibacterial, bioactivity, and others [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the degradation of injectable CaP is limited, thus hindering the growth of newborn bones, so introducing porous materials with an enhanced degradation rate would be necessary. In addition to natural sources, synthetic polymer-based biomaterials derived from a series of polymerization and crosslinking processes are designed purposefully with expected properties and functions, among which PLGA 87 and PCL 88 with nontoxic, gelling, filming, and capsuling properties have received widespread use. The properties of synthetic materials alone are slightly inferior, but when natural materials are introduced, a better bone repair result is realized.…”
Section: Bioactive Materialsmentioning
confidence: 99%
“…Several studies have investigated the effect of modified 3DP scaffolds in preclinical animal models. For example, Xu et al have investigated the effects of PDA coating on the osteointegration of 3DP PLGA/β-tricalcium phosphate (TCP) scaffolds [ 144 ]. The results indicated that the PDA coating significantly increased the attachment and spreading of pre-osteogenic cells in vitro.…”
Section: Melanins and Melanin-like Materials In Tissue Engineeringmentioning
confidence: 99%
“… Gross specimens ( a ) and micro-CT-reconstructed images ( b ) of experimental animals at 2 weeks and 6 weeks after bare or PDA-coated scaffold-implantation surgery. Reproduced with permission from [ 144 ]. Copyright Multidisciplinary Digital Publishing Institute (MDPI), 2019.…”
Section: Figurementioning
confidence: 99%